Adaptasi Sosial Tokoh Mikami dalam Film Subarashiki Sekai karya Miwa Nishikawa - Zaki Ainul Fadli; Nezatria Risma Quartyza (Universitas Diponegoro, 2022)
This research was conducted to reveal and classify the social adaptation efforts made by the main character in the film